2022
DOI: 10.1002/ueg2.12350
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of inflammatory bowel disease in Asia and Asian immigrants to Western countries

Abstract: Inflammatory bowel disease (IBD), which comprises Crohn's disease and ulcerative colitis, is an idiopathic inflammatory condition of the gastrointestinal tract. The incidence and prevalence of IBD are rapidly increasing worldwide, particularly in newly industrialized regions such as Asia. Although a large medical armamentarium is available for treating this chronic disease, IBD imposes a marked global disease burden. To understand the complex etiopathogenesis of this condition, it is important to consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 107 publications
(239 reference statements)
3
36
0
Order By: Relevance
“…1 To further understand the complex pathogenesis of IBD, it is crucial to focus on the recent changing trends of its epidemiology, especially in newly industrialized regions such as Asian countries. Aniwan et al 2 discussed the increased incidence and prevalence of IBD, in the last decades, in both Asian countries and Asian immigrants in western countries. The discussion of this data shall consider that this population exhibits a unique disease phenotype, with a high rate of perianal disease in Crohn's disease (CD).…”
Section: Epidemiology and Risk Factors Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…1 To further understand the complex pathogenesis of IBD, it is crucial to focus on the recent changing trends of its epidemiology, especially in newly industrialized regions such as Asian countries. Aniwan et al 2 discussed the increased incidence and prevalence of IBD, in the last decades, in both Asian countries and Asian immigrants in western countries. The discussion of this data shall consider that this population exhibits a unique disease phenotype, with a high rate of perianal disease in Crohn's disease (CD).…”
Section: Epidemiology and Risk Factors Of Ibdmentioning
confidence: 99%
“…Aniwan et al. 2 discussed the increased incidence and prevalence of IBD, in the last decades, in both Asian countries and Asian immigrants in western countries. The discussion of this data shall consider that this population exhibits a unique disease phenotype, with a high rate of perianal disease in Crohn's disease (CD).…”
Section: Epidemiology and Risk Factors Of Ibdmentioning
confidence: 99%
“…Over the past 30 years, the incidence and prevalence of IBD have increased in China and other Asian countries. According to a South Korea survey, the OPEN ACCESS EDITED BY incidence of UC increased by approximately 20 times, and that of CD increased by about 40 times for 30 years from 1986 to 2015 (Aniwan et al, 2022). A Chinese survey revealed that the number of IBD cases in China increased by approximately 3 times from 1990 to 2019 (Shao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, after the 1990s, the adoption of a western lifestyle led to significant increases in cases of the disease in these regions. Moreover, immigrants who move to developed countries represent a unique population in which the risk for IBD evolves over subsequent generations to become comparable to that in the host country eventually [ 5 , 6 ]. Several studies conducted on large groups of Mexicans living in the US and Indians settled in Europe, the US, or the Middle East have shown large differences regarding incidence and prevalence compared to countries of origin, reflecting the impact of diet, pollution, or environmental factors on the epidemiology of the disease [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%